Direct Recycling of Nd–Fe–B Magnets Based on the Recovery of Nd(2)Fe(14)B Grains by Acid‐free Electrochemical Etching - Xu, Xuan (ChemSusChem, 2019)
Recycling of end‐of‐life Nd–Fe–B magnets is an important strategy for reducing the environmental dangers associated with rare‐earth mining and overcoming the supply risks associated with the rare‐earth elements. In this study, a novel concept for recycling of sintered Nd–Fe–B magnets by directly recovering the matrix Nd(2)Fe(14)B grains is presented. The procedure is based on the anodic etching of sintered Nd–Fe–B magnets in a nonaqueous dimethylformamide (DMF)/0.3 mol L(−1) FeCl(2) bath. Selective recovery of Nd(2)Fe(14)B grains was realized within the applied current density <5 mA cm(−2) based on the etching priority of phases: metallic Nd > intergranular NdFe(4)B(4) > matrix Nd(2)Fe(14)B. The total energy consumption of the proposed recycling route is estimated to be 2.99 kWh kg(−1), which is comparable to the state‐of‐the‐art methods. However, the proposed recycling route is currently the only procedure that enables repeated recycling of sintered Nd–Fe–B magnets in a closed‐loop system.